2019
DOI: 10.1002/mbo3.852
|View full text |Cite
|
Sign up to set email alerts
|

Genomic ecology of Marine Group II, the most common marine planktonic Archaea across the surface ocean

Abstract: Planktonic Archaea have been detected in all the world's oceans and are found from surface waters to the deep sea. The two most common Archaea phyla are Thaumarchaeota and Euryarchaeota. Euryarchaeota are generally more common in surface waters, but very little is known about their ecology and their potential metabolisms. In this study, we explore the genomic ecology of the Marine Group II (MGII), the main marine planktonic Euryarchaeota, and test if it is composed of different ecologically relevant units. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Archaea were well represented in all Tunisian coastal seawater samples (>10% of the prokaryotes) and were mainly composed of the candidate order "Poseidoniales" (MGII), as observed in coastal northwest Mediterranean Sea and in surface waters of different marine areas around the world (Galand et al, 2010;Hugoni et al, 2013;Pereira et al, 2019;Rinke et al, 2019;Santoro et al, 2019). In our winter study, the MGIIb group (Candidatus Thalassarchaeaceae, represented by the ASVs 3, 21, 29, 40) was more abundant that the MGIIa (represented by the ASVs 28 and 41) in seawaters.…”
Section: Discussionmentioning
confidence: 90%
“…Archaea were well represented in all Tunisian coastal seawater samples (>10% of the prokaryotes) and were mainly composed of the candidate order "Poseidoniales" (MGII), as observed in coastal northwest Mediterranean Sea and in surface waters of different marine areas around the world (Galand et al, 2010;Hugoni et al, 2013;Pereira et al, 2019;Rinke et al, 2019;Santoro et al, 2019). In our winter study, the MGIIb group (Candidatus Thalassarchaeaceae, represented by the ASVs 3, 21, 29, 40) was more abundant that the MGIIa (represented by the ASVs 28 and 41) in seawaters.…”
Section: Discussionmentioning
confidence: 90%
“…Thaumarchaeota MG I and Euryarchaeota MGIIb in the winter and Euryarchaeota MGIIa in the summer exist in various ecotypes in the coastal surface waters of the western Mediterranean Sea, characterized by different activity patterns (Hugoni et al 2013). Furthermore, several recent studies on the Euryarchaeota MGII group in coastal and open ocean systems identified diverse subclades with different ecological niches and lifestyles including members able to utilize taurine (Orellana et al 2019; Pereira et al 2019). Alteromonas phylo‐ and ecotypes also drastically differ in their utilization efficiencies of specific C‐compounds (Gómez‐Consarnau et al 2012; Sarmento and Gasol 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several excellent reviews and articles focussed on marine planktonic Archaea have recently been published ( Stahl and de la Torre, 2012 ; Zhang et al, 2015 ; Haro-Moreno et al, 2017 ; Pereira et al, 2019 ; Santoro et al, 2019 ; Baker et al, 2020 ), so readers are referred to those for more comprehensive overviews. This short Perspective deliberately focuses on a brief historical account of own my lab’s adventures in studying marine planktonic Archaea over the past 30 years.…”
Section: Introductionmentioning
confidence: 99%